Forget the Muse, think only of the (Decentered) Subject? - Jeyifo, Biodun (Tydskrif vir Letterkunde, 2011)
This essay involves an exploration of complex and fascinating acts of decentering and re-centering of writers in relation to traditional Muses as institutionalizations or sedimentations of artistic and intellectual inspiration in cultural tradition. Using the specific example of Wole Soyinka's much discussed appropriation of Ogun, the Yoruba god of war, metallurgy and creativity as a point of departure, the paper gives what is intended as a far more complex and even more contradictory relationship between Soyinka and this chosen Muse than what we typically encounter in the criticism and scholarship on the Nigerian dramatist's writings. This is done in two distinct though interlocking interpretive, discursive moves: first, by reading Soyinka's positive appropriation of Ogun against Derek Walcott's disavowal of the Muses of both Europe and Africa in the play, Dream on Monkey Mountain and in one of his most important essays, "The Muse of History"; and, secondly, by critically excavating Soyinka's own scathing and revisionary critique of Ogun as a Muse in his first major play, A Dance of the Forests. Building on these readings of Soyinka and Walcott, the essay ends with a plea for paying as much attention, in the postcolonial Nigerian and African context, to re-centering as is given to decentering in Western postmodernist discourses, always with an eye to the interpenetrations and exchanges that take place among the diverse literary and cultural traditions of the world.